Trastornos hipertensivos del embarazo asociado a gestantes de 14 hasta 45 años atendidas en el Hospital León Becerra Camacho-Milagro primer semestre del 2018 - Vera Fajardo, Susety Lissette (2018)
Background: These gestational hypertensive disorders are responsible for 200,000 maternal deaths per year worldwide and are related to the significantly increased risk of maternal-perinatal death, the causes are multiple such as poor control, socioeconomic status, lifestyles among others. In 2018 in Ecuador the main cause of mortality is due to Sepsis and 30% Haemorrhages; maternal mortality from other causes 25%; maternal death Indirect 10% and maternal deaths due to Hypertensive Diseases 5%. Objectives: To establish the hypertensive disorders of pregnancy and their association to pregnant women from 14 to 45 years of age served in the Hospital León Becerra Camacho-Milagro first semester of 2018. Methodology: The research work on Hypertensive Disorders of Pregnancy associated with pregnant women from 14 to 45 years of age served in the Hospital León Becerra Camacho-Milagro first semester of 2018, is descriptive, non-experimental, retrospective, and observational. Population: The Study Population corresponds to the total of 1150 patients treated in the area of Obstetrics-Gynecology at the León Becerra Camacho-Milagro Hospital, first semester of 2018. Sample: The study sample includes 110 pregnant patients with hypertensive disorders who entered the León Becerra Camacho-Milagro Hospital first semester of 2018. Result: The results obtained in the research show that 43.63% had mild pre-eclampsia, 42.72% had Severe Preeclampsia, and 4.53% had Chronic Hypertension with Preeclampsia or Eclampsia